Application of validated LC-MS/MS method development to quantify pexidartinib in biological media: In-vivo bioavailability studies in healthy rabbits - Ayesha Begum Khadernaick, Kumar Shiva Gubbiyappa (Journal of Applied Pharmaceutical Science, 2021)
A specific liquid chromatographic with tandem mass spectrometric technique was established and validated for the analysis of pexidartinib in plasma samples. These samples were presented by selecting liquid–liquid extraction process with ethyl acetate. The procedure was established and subjected for validation with respect to the parameters’ specificity, sensitivity, carryover, recovery, precision, matrix effect, accuracy, and stability. Pexidartinib and Ledipasvir were eluted within 6.5 minutes on ZorbaxSB-C18 column (250 × 4.6 mm × 5 μm) with formic acid (0.1% v/v) and acetonitrile in the proportion of 20:80 in the movable phase with 0.9 ml/minutes infusion flow rate. This analytical method was also applied successfully to assess the bioavailability studies in six healthy rabbits. From in-vivo bioavailability studies, pexidartinib showed Tmax of 3.09 ± 0.14, and mean Cmax and AUC0→last for test formulation were 211.63 ± 11.045 and 4,448.8 ± 257.892, respectively.
Keywords: Pexidartinib, Giant cell tumor, LC–MS/MS, healthy rabbits and bioavailability studies.